PENGARUH LKS FISIKA PADA ICT MENGINTEGRASIKAN MSTBK TOPIK GETARAN HARMONIS, MOMENTUM DAN IMPULS TERHADAP KOMPETENSI FISIKA SISWA KELAS XI SMAN 1 LUBUK ALUNG - Iing Pebrika; Akmam Akmam; Harman Amir (PILLAR OF PHYSICS EDUCATION, 2015)
Graduated in formal education who have good character, good spiritual and social attitude, knowledge and skillful were needed in globalization era. In fact not all of graduated students were capable competitedzation era. This condition was caused by character value and other science didn’t integrate in learning process yet. An alternative solution to solve this problem was applied the ICT woksheet by integrating Mathematics, Science, technology, disaster, and character value (MSTDC). The purpose of this research were to determine the competency of the Physics students and to investigate the effect of ICT woksheet by integrating MSTDC to the competency of Physics students grade XI  at SMAN 1 Lubuk Alung. The population of quasi experimental research were the students grade XI MIA SMAN I Lubuk Alung in the 2014/2015 academic year. Sampling was taken by purposive sampling technique. The research instrument were the test sheet for competency domain of knowledge, observation sheet for competency domain of attitude, and performance sheet for competency domain of skills. Based on the data analysis could be presented the conclusions of this research. First, there was significant differention competency of students between two sampling classes that were in same condition, except the worksheet which was used. Second, the use of ICT worksheet by integrating MSTDC gave significant effect toward Physics competency of students grade XI at SMAN 1 Lubuk Alung